Appendix 4.11: Marcos Diary Entry, 11 October 1972 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Another meeting with Justice Fred Ruiz Castro is actually only a minor detail in this entry. The bulk of it is about consolidating forces against the secessionists in the south and subversion in the north, and, after claiming that the Lopezes have relatives of justices in their payroll, Marcos focuses on his propaganda efforts abroad, specifically via Richard Critchfield in the United States.